A alternância republicana no parlamento: um olhar sobre a (re)eleição de veteranos políticos no Brasil - Cavarzere, Caroline Rodrigues (2021)
This research analyzes the republican principle, from the many republican concepts addressed by the doctrine, to republican movement in Brazil and in the occidental world, in order to better understand its implementation in Brazilian society, with the purpose to compare these studies with the minimal alternation of political power in the National Congress, from neo-constitutionalism perspective. To this end, this Master’s dissertation verifies, election by election, from 1990 to 2018, the number of new and experienced deputies and senators chosen by the people, graphically demonstrating, predominance of veterans and lack of new voices exercising Legislative Power. Given the normative dimension of the principals, this study explores Brazilian Constitutions since 1891 and current legal system, in search of republican principle realization and of positive State actions to make it concrete in real life. The main objective is to analyze whether the State is failing in its duty to materialize the principal in perspective, by not setting limits on the possibility of reelections. This research uses the inductive scientific method, by documentary research and review, with the support of statistical and historical methods.